Workability and durability analysis of waste based geopolymer concrete - Lucia Omolayo Agashua; Chinwuba Arum; Bamitale Dorcas Oluyemi- Ayibiowu; Catherine Mayowa Ikumapayi (SINERGI, 2024)
GPC as a promising material, started gaining momentous attention from the researchers and construction specialists because of its advantages in using by-products from agriculture and industries to replace cement thereby reducing greenhouse gas emission. Workability and durability tests were carried out, so as ascertain the efficiency of the rice husk ash and rice husk as sodium silicate and super plasticizer, for solving efflorescence problem known with geopolymer concrete.  The factory-made sodium silicate was also used and compared with laboratory-produced, before addition of other geopolymer binders such as kaolin clay and fly ash. Brunauer-Emmett-Teller (BET) scrutiny that delivers quantitative data on the specific surface area as well as porosity dispersal of solid materials revealed that correlation coefficient of RHA (0.994) was higher than that of cement (0.991).  Besides, RHA has higher surface area (250.023 m3/g) than the cement utilized which stood at 211.49 m3/g. Though the c constant of cement exceeds the RHA values, RHA can serve as good pozzolanic material and cement substitute. It is seen that the workability of laboratory-produced sodium silicate and superplasticizer geopolymer concrete was enhanced significantly compared to that of prior geopolymer systems. It is observed that the workability of the geopolymer concrete was considerably enhanced compared to that of orthodox geopolymeric systems, especially at 2.5% rice-husk created superplasticizer and higher content of laboratory-produced sodium silicate.